Mind-blanking: when the mind goes away - Ward, Adrian F.; Wegner, Daniel M. (Frontiers in Psychology, 2013)
People often feel like their minds and their bodies are in different places. Far from an exotic experience, this phenomenon seems to be ubiquitous facet of human life (e.g., Killingsworth & Gilbert, 2010). Many times, people’s minds seem to go “somewhere else”—attention becomes disconnected from perception, and people’s minds wander to times and places removed from the current environment (e.g., Schooler, Reichle & Halpern, 2004). At other times, however, people’s minds may seem to go nowhere at all—they simply disappear. This mental state—mind-blanking—may represent an extreme decoupling of perception and attention, one in which attention fails to bring any stimuli into conscious awareness. In the present research, we outline the properties of mind-blanking, differentiating this mental state from other mental states in terms of phenomenological experience, behavioral outcomes, and underlying cognitive processes. Seven experiments suggest that when the mind seems to disappear, there are times when we have simply failed to monitor its whereabouts—and there are times when it is actually gone.